Penilaian dampak Balance of Power antara Tiongkok dan India terhadap Ekonomi dan Perdamaian Global. - Yahaya, Jibrin Ubale (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The rise of China and India as two emerging world powers was an attempt to test the capabilities of the two new contemporary strong economic countries moving in to new paradigm of global economic order in next coming 20 years. As the two powerful countries grow up, they are surrounded with challenges from the United State and its alliance in trying not to give a chance for new global power to emerge. The major objective of this study is to make an evaluation on the rational of Chinese and India development global perspective in the circle of changing the direction of international system order from the West to the Asia -Pacific region. China and India tend to agree on the significance of state sovereignty and has the same notion of reforming global governance institutions to reflect the new balance of power. The two countries also share a strong commitment to the open economic order that has allowed both powers to flourish in the global marketplace. But the two diverge on many details of the international system, such as the future viability of the Non-Proliferation Treaty and the role of state-owned enterprises in fostering globalization process